2016
DOI: 10.1038/srep24030
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of the gut resistome after a gut microbiota-targeted dietary intervention in obese children

Abstract: The gut microbiome represents an important reservoir of antibiotic resistance genes (ARGs). Effective methods are urgently needed for managing the gut resistome to fight against the antibiotic resistance threat. In this study, we show that a gut microbiota-targeted dietary intervention, which shifts the dominant fermentation of gut bacteria from protein to carbohydrate, significantly diminished the gut resistome and alleviated metabolic syndrome in obese children. Of the non-redundant metagenomic gene catalog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
0
38
0
1
Order By: Relevance
“…The mechanisms of colonization resistance include nutrient competition and direct bactericidal activity, immune stimulation, and various aspects of metabolic activity (120)(121)(122). Diet shifts may be associated with decreases in the types of organisms that often carry ARGs (123). When further elucidated, these mechanisms are likely to provide good leads for informed interventions to counter the burden of AMR.…”
Section: Future Directionsmentioning
confidence: 99%
“…The mechanisms of colonization resistance include nutrient competition and direct bactericidal activity, immune stimulation, and various aspects of metabolic activity (120)(121)(122). Diet shifts may be associated with decreases in the types of organisms that often carry ARGs (123). When further elucidated, these mechanisms are likely to provide good leads for informed interventions to counter the burden of AMR.…”
Section: Future Directionsmentioning
confidence: 99%
“…As the pipeline of research into antimicrobial agent, with a few exceptions, seems to dry up, dietary interventions are under active consideration for the time being. In Wu et al (2016) showed in their study that a gut microbiota-targeted dietary intervention in obese children managed not only to alter the composition and functionality of the intestinal microbiome but, furthermore, to remarkably decrease their gut resistome. The diet that they had previously implemented (Zhang et al, 2015) included whole grains, traditional Chinese medicinal foods, and prebiotics (WTP diet), and with a genome-centric metagenomic approach, this resulted in a reduction of body weight and inflammation parameters.…”
Section: Resistome Diminution Due To Dietary Supplementation -Is It Fmentioning
confidence: 99%
“…The diet that they had previously implemented (Zhang et al, 2015) included whole grains, traditional Chinese medicinal foods, and prebiotics (WTP diet), and with a genome-centric metagenomic approach, this resulted in a reduction of body weight and inflammation parameters. According to their data, other than weight loss and health improvements, they reported a decrease of the resistome richness, a reduction in the AR gene members, and the diminution of multiple-resistance AR gene carriers (reduced 69%), showcasing a possible novel perspective for the issue (Wu et al, 2016). Another important notion in this study is that, because of the diet type (high carbohydrate), Bifidobacterium was augmented and had few or no ARgenes, whereas the decreased bacteria resembled a minefield with their great burden combined with the final reduction of the resistome.…”
Section: Resistome Diminution Due To Dietary Supplementation -Is It Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, how to regulate the gut microbiota of obese individuals by diet [11,12], drugs, or probiotics and prebiotics [13], attracts scienti c attention.…”
Section: Introductionmentioning
confidence: 99%